Antifungal Activity of Polyphenolic Complex of Acacia nilotica Bark - Bhargava, Alka; Srivastava, Anubha; Kumbhare, V. (Indian Forester, 1998)
The antifungal activity of polyphenolic complex (PC) of Acacia nilotica bark on Fusarium oxysporum was tested at 50%, 25% and 10% dilution by measuring the mycelial growth. The extract of 50% concentration showed maximum growth inhibition (56%) as compared to control. The phytochemical analysis of bark extract showed presence of phenols, flavones, tannins and glycosides in the PC. Total phenols and tannin content in the dried bark sample were found to 9.86 g and 13.40 g and total flavonols and total o-dihydric phenols including chiorogenic acid were only 0.0025 g and 0.013 g per 100 g. The antifungal activity of the bark has been attributed to the presence of polyphenolic substances.